PENGARUH METODE PROBLEM SOLVING TERHADAP HASIL BELAJAR TEMATIK KELAS V SEKOLAH DASAR - Yuniansih Yuniansih; Kartono Kartono; Dyoti Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to analyze the effect of problem solving methods on thematic learning on learning outcomes of fifth grade students at Pontianak Elementary School 66 Pontianak City. The research method used was an experimental research quasi experimental design, with the experimental design of nonequivalent control group design. The population of this study was all students of class V SD Negeri 66 Pontianak Kota. The sample is determined by total sampling technique, to determine the experimental class and the control class randomly selected by drawing the VB class as many as 36 students as the control class and VA as many as 37 students as the experimental class. Data collection techniques using measurement techniques. The instrument used was a test sheet in the form of multiple choice learning totaling 50 questions. Based on calculations obtained the average post-test learning outcomes of the control class 66.61 and the average post-test learning outcomes of the experimental class 73.62 so that the post-test data of 3.936 was obtained with a table for the significance level (α = 5% and dk = 37 + 36-2 = 71) of 1.996, because tcount> ttable then Ha is accepted, this proves that there is an effect of problem solving methods on thematic learning towards learning outcomes of class V students of 66 Pontianak Elementary School. From the calculation of the effect size obtained by 0.63 including the criteria of being, so it can be concluded that the method of problem solving in thematic learning has a moderate effect on learning outcomes of students of class V 66 State Primary School Pontianak City.                                     Keywords :  Learning Outcomes ,  Problem Solving Methods, and Thematic Learning